CLINICAL STRUCTURE AND REVELATION OF TUBERCULOSIS WITHIN TENSE EPIDEMICAL SITUATION IN MOSCOW - A.V. Filippov; E.S. Ovsyankina (Вопросы современной педиатрии, 2011)
The article analyzes dynamics of incidence of tuberculosis in children 0–14 years old in Moscow (1993–2000 years). The role of antituberculosis healthcare services in revelation of infected children increases while the participation of general healthcare services in this process becomes low. The structure of tuberculosis in children according to clinical forms and revelation methods is studied. Changes in group structure of revealed patients with relative stabilization of children’s morbidity come due to increase of secondary tuberculosis rate and late diagnostics of out-of-pulmonary disease.Key words: children, tuberculosis, morbidity, diagnostics.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2011; 10 (3): 76–79)